α-Tocopherol Modulates Non-Amyloidogenic Pathway and Autophagy in an In Vitro Model of Alzheimer’s Disease: A Transcriptional Study - Agnese Gugliandolo; Luigi Chiricosta; Serena Silvestro; Placido Bramanti; Emanuela Mazzon (Brain Sciences, 2019)
Alzheimer’s disease (AD) is the most common form of dementia worldwide. The hallmarks of AD are the extracellular amyloid plaques, which are formed by amyloid β (Aβ) aggregates derived from the processing of the amyloid precursor protein (APP), and the intraneuronal neurofibrillary tangles, which are formed by the hyperphosphorylated tau protein. The aim of this work was to study the effects of α-tocopherol in retinoic acid differentiated SH-SY5Y neuroblastoma cells exposed to Aβ1-42 evaluating the transcriptional profile by next-generation sequencing. We observed that α-tocopherol was able to reduce the cytotoxicity induced by Aβ treatment, as demonstrated by Thiazolyl Blue Tetrazolium Bromide (MTT) assay. Moreover, the transcriptomic analysis evidenced that α-tocopherol treatment upregulated genes involved in the non-amyloidogenic processing of APP, while it downregulated the amyloidogenic pathway. Moreover, α-tocopherol modulated the expression of the genes involved in autophagy and the cell cycle, which are both known to be altered in AD. The treatment with α-tocopherol was also able to reduce oxidative stress, restoring nuclear factor erythroid-derived 2-like 2 (Nrf2) and decreasing inducible nitric oxide synthase (iNOS) levels, as demonstrated by immunocytochemistry.